ANALISIS PERSEPSI DAN KEPUASAN KONSUMEN RESTORAN PECEL LELE LELA - Doni Sahat Tua Manalu (Jurnal Hexagro, 2020)
Pecel Lele Lela was founded in 2006 and has been awarded as an effort to introduce the most innovative catfish from the Indonesian Ministry of Fisheries and Maritime Affairs. This is the background of this research, while the purpose of this research is to find out how customers' perceptions and satisfaction of Pecel Lele Lela Restaurant, one of the methods that can be used is Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI) method. Based on the data validity test, obtained 5 (five) attributes on the questionnaire are invalid, while for the reliability test states that all aspects studied are reliable. The results of the analysis of consumer perception of Pecel Lele Lela Restaurant indicate that the dimensions according to consumers are important are the dimensions of responsiveness and empathy. Based on the results of the Performance Analysis Index analysis, the attributes that need to be improved and prioritized to be addressed are the stand-by waiter in responding to consumers, setting prospective customers when waiting-list, and the waiter immediately cleans the dining table when the consumer finishes eating. Based on the calculation of the Customer Satisfaction Index, the level of customer satisfaction of Pecel Lele Lela Restaurant is 79.738%. These results certainly become the basis for evaluating Pecel Lele Lela Restaurant to improve and improve the attributes that are the top priority of the restaurant